Determinasi Artificial Intelligence Akuntansi Dalam Pembuatan Laporan Keuangan Bagi Pemilik Sarana Apotek di Kota Bandar Lampung - Wahyuni, Sinta Dwi; Puspitasari, Endah Yuni; Wijaya, Lihan Rini Puspo (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the determinants of artificial intelligence (AI) use in accounting for Pharmacy Service Owners (PSA) in Bandar Lampung City. The methodology employed is a quantitative approach and uses the SPSS version 26 application, distributing questionnaires to 100 respondents selected through purposive sampling. Hypothesis testing uses multiple linear analysis to examine what factors influence the application of accounting artificial intelligence. The result of the study indicate that the benefits of accounting obtain a value (coefficient 0,160, t-statistic 3.143) influencing the need for the application of accounting AI in the preparation of financial reports and basic techniques obtain a value (coefficient 0,117, t-statistic 2,820) influencing the need for the application of accounting AI in the preparation of financial reports and stakeholder obligations obtain a value (coefficient 0,104, t-statistic 2,046) influencing the need for the application of accounting AI in the preparation of financial reporting. PSA's knowledge of accounting benefits and technical fundamentals, as well as obligations from stakeholders, significantly contribute to technology adoption. The conclusion of this research emphasizes the importance of better understanding accounting and applying AI to enhance the efficiency and accuracy of financial reports in the pharmacy sector, encouraging PSAs to leverage modern technology for better business growth.